A Personality-Based Approach to Understanding Achievement Motivation in Professionals - Aich, Subhajit; Kundu, Srijani; Biswas, Agnikana; Dutta, Priyadev; Chakraborty, Alokananda (Journal of Neonatal Surgery, 2025)
The aim of the present study is to explore the link between personality and achievement motivation in working personnel. 103 participants (41 female, 62 males) were assessed on AMS & TIPI and Regression analysis was conducted along with other descriptives using SPSS. Result shows that ‘Emotional stability’ is a significant positive predictor of ‘hope for success’ and ‘Agreeableness’, ‘Emotional stability’, ‘Openness to experiences’ are significant negative predictors of ‘fear of failure’ in working personnel. So, Emotional stability or the opposite pole- Neuroticism is a common significant predictor of both types of achievement motivation